PEMBENTUKAN KARAKTER CINTA LINGKUNGAN DI SDN MARGOREJO 1/403 SURABAYA - Shofi Putri Silasari; Apri Irianto; Pana Pramulia (LPPM Universitas Cipta Mandiri, 2022)
This research is motivated by environmental problems that occur. This is due to a lack of knowledge and understanding related to the environment. Concern for the environment can be instilled through the character education of love of the environment, especially in school. Planting environmental love character education to elementary school students can be done by providing programs related to the character of environmental love. The goals to be achieved in this study include: describing the formation of environmental love character in SDN Margorejo 1/403 Surabaya, describing the implementation of environmental love character formation programs in SDN Margorejo 1/403 Surabaya, and describing obstacles in the implementation of environmental love character formation in SDN Margorejo 1/403 Surabaya. The approach used in this study is a qualitative approach. The data used in this study is qualitative data on the formation of environmental love character in SDN Margorejo 1/403 Surabaya. The data sources in the study were principals, teachers, students, and student guardians, as well as supporting documents. The data collection techniques in this study are observation, interview, and documentation. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion withdrawal or verification. The results showed that the formation of environmental love character in SDN Margorejo 1/403 Surabaya was carried out through school culture in the form of routine activities (jumberling (clean friday environment), environmental webinars, jelantah oil collection, plastic waste, paper waste, beach clean action), integrated in learning, and school programs.